Strumpellin is a novel valosin-containing protein binding partner linking hereditary spastic paraplegia to protein aggregation diseases - Clemen, Christoph Stephan; Tangavelou, Karthikeyan; Strucksberg, Karl-Heinz; Just, Steffen; Manta, Linda; Regus-Leidig, Hanna; Stumpf, Maria; Reimann, Jens; Coras, Roland; Morgan, Reginald O.; Fernandez, Maria-Pilar; Hofmann, Andreas; et al. (Brain, 2010)
Mutations of the human valosin-containing protein gene cause autosomal-dominant inclusion body myopathy associated with Paget disease of bone and frontotemporal dementia. We identified strumpellin as a novel valosin-containing protein binding partner. Strumpellin mutations have been shown to cause hereditary spastic paraplegia. We demonstrate that strumpellin is a ubiquitously expressed protein present in cytosolic and endoplasmic reticulum cell fractions. Overexpression or ablation of wild-type strumpellin caused significantly reduced wound closure velocities in wound healing assays, whereas overexpression of the disease-causing strumpellin N471D mutant showed no functional effect. Strumpellin knockdown experiments in human neuroblastoma cells resulted in a dramatic reduction of axonal outgrowth. Knockdown studies in zebrafish revealed severe cardiac contractile dysfunction, tail curvature and impaired motility. The latter phenotype is due to a loss of central and peripheral motoneuron formation. These data imply a strumpellin loss-of-function pathogenesis in hereditary spastic paraplegia. In the human central nervous system strumpellin shows a presynaptic localization. We further identified strumpellin in pathological protein aggregates in inclusion body myopathy associated with Paget disease of bone and frontotemporal dementia, various myofibrillar myopathies and in cortical neurons of a Huntington's disease mouse model. Beyond hereditary spastic paraplegia, our findings imply that mutant forms of strumpellin and valosin-containing protein may have a concerted pathogenic role in various protein aggregate diseases.
Gesehen am 03.05.2023